An Investigation of Banks’ Sustainable Performance in Pakistan from the Internal and External Perspective - Muhammad Sadiq Malik, Sadiq (UNIMAS Institutional Repository, 2024)
This research aims to empirically investigate the impact of internal factors (efficiency, profitability, and risk management capability) and external factors (Gross Domestic Product (GDP), inflation, interest rate, and the exchange rate) on the sustainable performance of banks in Pakistan. The sustainable performance of the banking sector in Pakistan is affected due to these contributing factors which are impacting the economy. The contingency theory and environmental, social, and governance (ESG) model have been applied to the framework of this thesis. This is a cross-sectional study using five years panel data from 2016-2020 of 32 banks in Pakistan. The stationarity of the data was checked through a unit root test. The OLS Panel Methods; Random, and Fixed Effect Model were used for quantitative analysis and testing of hypotheses. Results indicate that internal and external factors significantly impact the sustainable performance of banks in Pakistan except for inflation, and interest rates. The outcome of the study indicates the vital role of these variables in ascertaining the overall sustainable performance of banks in Pakistan. Policymakers, management, and investors can assess sustainable performance through the same framework. This research is a pioneer in Pakistan by providing new avenues for future studies on banks' sustainable performance through internal and external perspectives and its contribution to the existing global literature.